Vitamin B12 - do we need it? - Krzysztof Mariusz Halczuk; Bolesław Tomasz Karwowski (Farmacja Polska, 2022)
Vitamin B12 is a name for a number of chemicals based on the structure of Corrin's rings. Its main source in the diet are animal foods, in particular: meat, fish, dairy products and eggs. Plant products are usually low in cobalamin. In the body, biochemical functions are performed by two compounds from this group: methylcobalamin and adenosylcobalamin. Methylcobalamin is a cofactor of methionine synthase, which plays a key role in homocysteine methylation in the cytosolic methionine-folate cycle. Inhibition of this process due to vitamin B12 deficiency results in a functional folate deficiency - a so-called "folate trap" characterized by the accumulation of 5-methyltetrahydrofolate and a deficiency of tetrahydrofolate. At the same time, homocysteine is not methylated, which is the cause of homocysteine accumulation and the deficiency of methionine, which is the source of methyl residues used, among others, for DNA methylation. Blockage of the methionine-folate cycle may result in conditions such as pernicious anemia, megaloblastic anemia, complex sclerosis of the spinal cord, polyneuritis, and optic nerve atrophy. The risk of atherosclerosis is also increased. This compound is a cofactor of the enzyme - methylmalonyl-CoA mutase, which catalyzes the transformation of L-methylmalonyl-CoA into succinyl-CoA, which is one of the main substrates of the Krebs cycle. Succinyl CoA is also a factor involved in the post-translational modification of proteins - succinylation. The most dangerous health effect of inhibiting the transformation of L-methylmalonyl-CoA into succinyl-CoA is methylmalonic acidosis, caused by the accumulation of methylmalonic acid, which is formed in place of succinyl-CoA. It can cause a number of disorders, such as hypotension, weakened immunity or progressive renal failure. Another disorder associated with the abnormalities of the mitochondrial mechanism of vitamin B12 is defective succinylation of proteins. This can cause, for example, an abnormality in the structure and function of proteins that make up steroid hormone receptors or the Tau protein, which is believed to be one of the causes of Alzheimer's disease. Vitamin B12, despite taking part in only two reactions as an enzyme cofactor, affects many different functions of the human body, such as fat metabolism, development of nervous tissue - including the brain, circulatory system functions or the first discovered property of cobalamin - the effect on hematopoiesis. It is worth noting that it is within the scope of research interests to determine the impact of its excess / deficiency on cell homeostasis